Реалізація стратегічних імперативів у розвитку торговельного підприємства - Костенюк, Ю.Б.; Ткаченко, М.О. (Вісник економічної науки України, 2021)
Методологія дослідження. Методами дослідження в даній роботі є: аналіз та синтез для виявлення ключових зовнішніх і внутрішніх факторів, що впливають на діяльність підприємства; метод наукового узагальнення; статистичні методи узагальнення інформації при дослідженні соціально-економічних явищ.
Результати. Проведено аналіз зовнішнього та внутрішнього середовища ТОВ «Бюро Вин» та на основі цього визначено стратегічні імперативи підприємства. Під час аналізу було виявлено основних конкурентів компанії в профільній ніші, визначено питому вагу споживання вина в групі алкогольних напоїв в Україні, а також сформовано та визначено внутрішні фактори впливу на діяльність підприємства. Визначено ринкову частку ТОВ «Бюро Вин» та можливості удосконалення внутрішнього потенціалу компанії.
Новизна. Новизною роботи є підхід до оцінки стратегічного положення підприємства та розробки на основі цього стратегічних імперативів, що полягає у всебічному розгляді екзогенних та ендогенних факторів.
Практична значущість. Практичну значущість роботи становить розробка стратегічних імперативів підприємства на основі аналізу впливу соціально-економічних явищ макромасштабу, розрахунку ринкової долі компанії та фінансової стабільності. Методология исследования. Методами исследования в данной работе являются: анализ и синтез для определения внешних и внутренних факторов, которые влияют на деятельность предприятия; метод научного обобщения; статистические методы обобщения информации.
Результаты. Проведен анализ внешней и внутренней среды ООО «Бюро Вин» и на основе этого определены стратегические императивы предприятия. В результате анализа были выявлены основные конкуренты компании в профильной нише, определен удельный вес употребления вина в группе алкогольных напитков в Украине, а также сформированы и определены внутренние факторы влияния на деятельность предприятия. Определены рыночная доля ООО «Бюро Вин» и возможности совершенствования потенциала компании.
Новизна. Новизна работы заключается в сформированном подходе оценивания стратегического положения предприятия и разработке на основе этого стратегических императивов, который заключается во всестороннем обзоре экзогенных и эндогенных факторов.
Практическая значимость. Практическая значимость работы заключается в разработке стратегических императивов предприятия на основе анализа влияния социально-экономических явлений макромасштаба, расчета рыночной доли компании и финансовой стабильности. Methods. Research methods include the method of scientific generalization, analysis and synthesis to identify key external and internal factors influencing the activities of the enterprise; statistical methods of generalization of information.
Results. The article analyzes the external and internal environments of LLC «Wine Bureau» and on this basis the strategic imperatives of the enterprise are determined. The analysis identified the company's main competitors in the profile niche, determined the share of wine consumption in the group of alcoholic beverages in Ukraine, as well as formed and identified internal factors influencing the company's activities. Determined the market share of the «Wine Bureau» and opportunities to improve the company`s internal potential. On the basis of strategic decisions, a decision tree was built, according to which the company's highest priority is entering new markets. Among the results were identified that the highest priority is given to the company's entry into new markets, as this is facilitated by the current situation. The company sufficiently uses its own potential and can increase its own market share, sales due to additional borrowed funds.
Novelty. The novelty of the work lies in the formed approach to assessing the strategic position of the enterprise and the development on the basis of this strategic imperatives, which consists in a comprehensive review of exogenous and endogenous factors.
Practical value. The practical significance of the work lies in the development of strategic imperatives of the enterprise based on the analysis of the impact of socioeconomic phenomena of macro-scale, calculation of the company's market share and financial stability. In conclusion, in the future it is possible to expand the set of methods that assess the strategic potential of the enterprise and contribute to the construction of a hierarchical structure of decisions. Further research will include the use of modern Internet-marketing technologies to analyze the enterprise and its environment.